Efficacy of calcitonin for treating acute pain associated with osteoporotic vertebral compression fracture: an updated systematic review - Boucher, Emily; Rosgen, Brianna; Lang, Eddy (Canadian journal of emergency medicine, 2020)
Acutely painful osteoporotic vertebral compression fractures are associated with hospitalization and mortality in older adults. Calcitonin may be an alternative to opioid or nonopioid analgesia for treating acute compression fracture pain in emergency and primary care settings. This review summarizes pain, function, and adverse events associated with calcitonin. We searched MEDLINE, EMBASE, The Cochrane Library, clinical trials registries, and reference lists of included studies. Eligible studies evaluated the effect of synthetic calcitonins (salmon, eel, and human) on pain scores in adults ≥60 years old with a recent atraumatic compression fracture. Two reviewers screened studies, extracted data, and allocated bias in duplicate. A random effects meta-analysis evaluated standard mean difference (SMD) and heterogeneity (I2). Of 1,198 articles screened, 11 were included (9 in the meta-analysis). Treatment lasted from 14 days to 6 months. Pain was lower in the salmon calcitonin group (100-200 IU IM or NAS, daily) than the control group with high certainty of evidence at week 1 (SMD, -1.54; 95% confidence interval [CI], -2.02 - -1.06; I2 = 52%), representing a number needed to treat of two. The analgesic efficacy of salmon calcitonin at 4 weeks was unclear due to substantial heterogeneity. There was low certainty evidence that calcitonin did not increase the overall risk of adverse events, including nausea and vomiting (risk ratio, 2.10; 95% CI, 0.87-5.08; I2 = 47%). Calcitonin is beneficial and appears safe for treating acute pain associated with compression fractures. Further studies may improve the certainty of evidence.